An Analytical Study of a Sample of Staff at the Oil Training Institute (مجلة المنصور, 2022)
The research aims to identify the role played by containment administration in promoting in promoting justice among workers in organization and in order to achieve this tack accreditation of higher containment management dimensions (Adlib ; Functional integration; Motivation and compensation teach support)and expression of organization justice by distributive justice procedural justice intuitive justice and the application of research in Oil trading institute if it is to obtain the necessary information through a questionnaire a surrey of 45individuols was conducted for the purpose of analyzing the answer and search using number of statistical methods ( arithmetic mean standard deviation relative importance the correlation coefficient regression in the light of the results obtained has been reached to asset of conclusions the most important role in the management of global containment promote organizations justice.